Análisis comparativo de las propiedades físicas y mecánicas de los ladrillos de arcilla como elemento constructivo proveniente de fábricas ubicadas en la zona norte del departamento del Valle del Cauca en Colombia (2021)
The production of construction materials must follow minimum quality parameters to ensure proper operation in the works. For this reason, there is a need to establish control processes that demonstrate the durability and compliance of the materials, so validate their properties and be used without any inconvenience. However, such manufacturing processes may vary, depending on the methods each company applies and the materials they implement, which can cause possible representative differences between the results of the material tests when compared to each other. The purpose of this research is to carry out a comparative analysis of clay bricks as a constructive element, coming from a set of small-scale production bricks, located in the north of the department of Valle del Cauca - Colombia, in relation to the quality parameters established in the Norma Técnica Colombiana (NTC 4205), by evaluating the physical and mechanical properties among which we have the determination of the mass , breakage module, compression resistance, water absorption, size measurement and roll measurement; based on the guidelines established by the Norma Técnica Colombiana (NTC 4017).